Exploring the contemporary issues of corporate share waqf model in Malaysia with the reference to the Waqaf An-Nur Corporation Berhad - Mohamed Asmy Mohd Thas Thaker,; Hassanudin Mohd Thas Thaker, (Penerbit Universiti Kebangsaan Malaysia, 2015)
The paper aims to explore the administration and management issues of Corporate Share Waqf Model through the experience of Waqaf An-Nur Corporation Berhad. The qualitative approach notably case study is used to obtain the experiences and perception on the current practice and the issues related to administration and management of Corporate Share Waqf Model. Based on the in-depth interview findings, this study reveals that Waqaf An-Nur Corporation Berhad as pioneer of Corporate Share Waqf model faces several issues in their administration and management. The taxation, regulation, forms of dividend payment and administration are found to be the main hurdles in administering and managing Corporate Share Waqf Model particularly in Malaysian Context. This study provides recommendations for the policy maker in order to address the issue of administration and management of Corporate Share Waqf Model.